Bromine‐Substituted Fluorene: Molecular Structure, Br–Br Interactions, Room‐Temperature Phosphorescence, and Tricolor Triboluminescence. (16th November 2018) - Wang, Jiaqiang; Wang, Can; Gong, Yanbin; Liao, Qiuyan; Han, Mengmeng; Jiang, Tianjiao; Dang, Qianxi; Li, Yaqin; Li, Qianqian; Li, Zhen
Abstract: Organic tribophosphorescence materials are rarely reported and the introduction of Br atoms may be a practical way to design such materials. Here four bromine‐substituted fluorene‐based derivatives are presented and BrFlu−CBr, having fluorescence‐phosphorescence dual‐emission induced not only by UV light but also by mechanical stimulus, manifests the highest phosphorescence efficiency of 4.56 % upon photoirradiation. During the grinding process, three different triboluminescent spectra were identified. Upon introduction of a mechanical stimulus, the triboluminescence emission is cyan, whereas after an extended period it changed to blue. After removing the mechanical stimulus, green‐white phosphorescent emission was observed. Careful research on single‐crystal structures and theoretical calculations demonstrate that strong Br⋅⋅⋅Br interactions are vital to facilitate spin‐orbit coupling and promote intersystem crossing, thus generating the unique properties. Abstract : Ohne UV‐Anregung zeigen Kristalle des Fluorenderivats BrFlu−CBr sowohl Fluoreszenz als auch Phosphoreszenz als Antwort auf einen mechanischen Reiz. Wird dieser Reiz für längere Zeit aufrechterhalten, so wechselt die abgestrahlte Tribolumineszenz ihre Farbe von Cyan zu Blau. Nach Beendigung des Reizes wird eine grünweiße Phosphoreszenz beobachtet.